Integrated Uncertainty in Knowledge Modelling and Decision Making International Symposium, IUKM 2013, Beijing, China, July 12-14, 2013. Proceedings - Qin, Zengchang; Huynh, Van-Nam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Symposium on Integrated Uncertainty in Knowledge Modeling and Decision Making, IUKM 2013, held in Beijing China, in July 2013. The 19 revised full papers were carefully reviewed and selected from 49 submissions and are presented together with keynote and invited talks. The papers provide a wealth of new ideas and report both theoretical and applied research on integrated uncertainty modeling and management.
Keywords: Computer science; Computer software; Data mining; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity